2004
DOI: 10.1352/0047-6765(2004)42<294:soabmc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Significance of a Bar/Bat Mitzvah Ceremony for Parents of Jewish Children With Developmental Disabilities

Abstract: In the Jewish religion, a bar or bat mitzvah ceremony is the rite of passage from childhood towards adulthood. Twenty-one youngsters who attended two special education schools in Israel participated in group bar/bat mitzvah ceremonies. Parents were interviewed both before the learning process and after the ceremony. Findings showed that the bar/bat mitzvah experience was a positive multidimensional one. Dimensions identified were bar/bat mitzvah as a transition, a normative, and a religious experience; an even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In an interesting article, Vogel and Reiter (2004) specifically discussed the role of the bar or bat mitzvah ceremony for people with intellectual disability. They noted that celebrating a bar or bat mitzvah had significance on six dimensions for families of children with intellectual impairment: bar or bat mitzvahs were viewed as transitions (a rite of passage), normative experiences (we celebrate like everyone else), religious experiences (i.e., involvement in the spiritual and ritual aspects of being called up to the Torah, leading a prayer), inclusive experiences (family members were invited, a life experience was shared with others), experiences leading to an et^hancement of self-image (the adolescents saw it as an opportunity to show they are capable and feel mature), and as peak life experiences (providing an opportunity to celebrate the child, providing the child with a pleasant memory).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an interesting article, Vogel and Reiter (2004) specifically discussed the role of the bar or bat mitzvah ceremony for people with intellectual disability. They noted that celebrating a bar or bat mitzvah had significance on six dimensions for families of children with intellectual impairment: bar or bat mitzvahs were viewed as transitions (a rite of passage), normative experiences (we celebrate like everyone else), religious experiences (i.e., involvement in the spiritual and ritual aspects of being called up to the Torah, leading a prayer), inclusive experiences (family members were invited, a life experience was shared with others), experiences leading to an et^hancement of self-image (the adolescents saw it as an opportunity to show they are capable and feel mature), and as peak life experiences (providing an opportunity to celebrate the child, providing the child with a pleasant memory).…”
Section: Resultsmentioning
confidence: 99%
“…Bailey, 2001) and (b) the use of religion (but not necessarily spirituality) in the communal lives of people with intellectual disability (that is, how to include people with specialized needs in, for example, congregations, life rituals, rites of passage) (Vogel & Reiter, 2004). There is very little published research, however, on the spiritual life of people with intellectual disability themselves.…”
Section: Spirituality In the Lives Of People With Intellectual Disabimentioning
confidence: 99%
“…A revealing qualitative study of Jewish children, with developmental disabilities participating in their bar/bat mitzvah ceremonies, illustrated that the "youngsters could both express their own spirituality and impact the spirituality of others" (Vogel and Reiter, 2003). This again highlights the importance of clinicians exploring whether people with an intellectual disability have been involved as much as possible in ceremonies and services that are in keeping with their religious faith and culture.…”
Section: Involvement In Religious Services and Faith Groupsmentioning
confidence: 99%
“…Carmeli and Carmeli (2001) used intensive teaching of holiday (holy-day) awareness to Jewish youngsters with moderatesevere LD using object signifiers. In early adolescence, Vogel and Reiter (2003) report preparation and meaningful participation of youngsters with a wide range of disability in Bar/Bat Mitzvah while Bunnin and Steel (2006) explored self-concept using Talking Mats with Jewish students, finding that ''being young,'' ''having a learning disability'' and ''being Jewish'' formed closely intertwined narratives. Comparing students with learning disability with others functioning intellectually in the borderline range, Lifshitz and Glaubman (2007) showed that the former also observe religious commandments out of personal choice, despite showing difficulties with commandments requiring control over eating, such as fasting.…”
Section: Spirituality In Healthcarementioning
confidence: 99%